Assessment of habitat suitability and connectivity across the potential distribution landscape of the sambar (Rusa unicolor) in Southwest China - Wang, Pan; Feng, Bin; Zhang, Li; Fan, Xueyang; Tang, Zhuo; Dong, Xin; Zhang, Jindong; Zhou, Caiquan; Bai, Wenke (Frontiers in Conservation Science, 2023)
Habitat suitability assessment is the basis for wildlife conservation management and habitat restoration. It will help to understand the quality of the wildlife habitat and its potential spatial distribution. This study collected records of sambar (Rusa Unicolor) from over 2,000 camera traps’ locations in the forests of southwest China in the past five years to assess the overall situation of its habitat. The results of the species distribution model revealed that the suitable habitat area of sambar in the five major mountains (Minshan, Qionglai, Daxiangling, Xiaoxiangling, and Liangshan) in Southwest China is 18,231 km2, accounting for 17.02% of the total area. And the most suitable habitat of sambar is mainly distributed in the Qionglai, as well as the intersection area of Daxiangling, Xiaoxiangling and Minshan. Moreover, the temperature annual range, temperature seasonality, elevation, and distance to road were important factors affecting the distribution of suitable habitat for sambar. Analysis of landscape pattern shows that there were 273 habitat patches, with a maximum patch area of 9,983 km2, accounting for 54.8% of the total suitable habitat area. However, the segmentation index and separation index of each habitat patch were 0.99 and 106.58, indicating a relatively high habitat fragmentation in the study area. The results of habitat connectivity analysis show that the Qionglai Mountain has the largest suitable habitat area and the highest connectivity of habitat patches. And the connectivity of habitat patches between the five mountains is very low, which means population diffusion is difficult between the mountains. This shows the need to strengthen the sambar and their habitat protection in the future, especially the establishment of corridors between the different mountain populations.